Religious Rationalization of Ziarah Kubur Among Indonesian Students in Cairo - Zainal Fanani; Arfan Maskuri (An-Nur International Journal of Islamic Thought, 2025)
This study investigates the practice, motivation, and meaning-making of grave pilgrimage (ziarah kubur), a prominent Indonesian religious tradition, among Indonesian university students in Cairo, Egypt. It aims to understand how this cultural practice is maintained, negotiated, and rationalized within a major center of Islamic scholarship. Employing a qualitative-dominant research design, this study analyzed survey narratives from 54 Indonesian students, supported by descriptive statistics. The findings reveal that grave pilgrimage is widespread, serving as a key mechanism for cultural identity preservation in a diaspora context. The motivations are identified as a dynamic interplay between personal spiritual needs, such as seeking tranquility and divine blessings (barakah), and the reinforcement of communal cultural sentiments. Crucially, the study uncovers a sophisticated process of 'religious rationalization,' whereby students utilize their formal religious education to re-frame the practice intellectually, shifting it from the category of local custom (adat) to a more universally justifiable act of worship (ibadah). This research concludes that for this cohort of future religious elites, grave pilgrimage is not a static tradition but a dynamic, adaptive strategy for negotiating their Indonesian and Muslim identities. The practice is intellectually reinforced, ensuring its continued relevance and vitality in a transnational context.